2016
DOI: 10.22211/cejem/64988
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Catalyst in the HBIW Hydrodebenzylation Reaction. Deactivation and Spent Catalyst Regeneration Procedure

Abstract: Abstract:The BAM-Fallhammer is a mechanical device to test the impact sensitivity of explosives and to determine a sensitiveness level. By its construction it transforms potential energy into kinetic energy of an impacting hammer, then hitting the sample. Ideally the entire potential energy is available at the moment of impact and the supporting base is infinitely rigid. By this study we want to quantify how much a real Fallhammer deviates from the ideal concept, and what the differences between different Fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The intermediate after debenzylation should be acetylated by Ac 2 O to avoid the ring opening of the isowurtzitane, and TADBIW can be obtained after the HBIW undergo four cycles of debenzylation‐acetylation. As a result, the hydrogenolysis of HBIW required extremely efficient catalysts to accelerate the cycles of debenzylation‐acetylation, which can reduce the negative effect of the fragile stability of the intermediates [27–29] …”
Section: Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermediate after debenzylation should be acetylated by Ac 2 O to avoid the ring opening of the isowurtzitane, and TADBIW can be obtained after the HBIW undergo four cycles of debenzylation‐acetylation. As a result, the hydrogenolysis of HBIW required extremely efficient catalysts to accelerate the cycles of debenzylation‐acetylation, which can reduce the negative effect of the fragile stability of the intermediates [27–29] …”
Section: Results Discussionmentioning
confidence: 99%
“…As a result, the hydrogenolysis of HBIW required extremely efficient catalysts to accelerate the cycles of debenzylation-acetylation, which can reduce the negative effect of the fragile stability of the intermediates. [27][28][29] The catalytic performance of the as-obtained Pd/g-C 3 N 4 NS on the hydrogenolysis of HBIW was examined. The hydrogenolysis of HBIW was conducted under atomspheric pressure and the conversion of HBIW was monitored by UPLC (Fig- ure S2).…”
Section: Catalytic Performancementioning
confidence: 99%
“…The hydrogenolysis of HBIW was implemented in a 150 mL reaction vessel via magnetic stirrer and heated with a water bath as reported. ,,, The parameters were 500–600 rpm and 0.40 MPa. Typically, 2.5 mL of DMF, 1.5 mL of Ac 2 O, 0.02 mL of PhBr, 1.0 g of HBIW, and 0.05 g of catalysts were placed into the reactor.…”
Section: Methodsmentioning
confidence: 99%
“…The cleavage of the C–N bond via hydrogenolysis is one of the most frequently used deprotecting classifications for amino functionalities with benzyl groups in the fields of fine chemistry as well as pharmaceuticals and the military. The hydrogenolysis reactions are commonly based on heterogeneous Pd-based catalysts. However, some significant problems for practical application often appear, such as low yields for some special debenzylation reactions, , a high precious metal loading and usage amount, and poor stability. Varieties of Pd particle catalysts have to be explored in order to improve the cost efficiency of debenzylation processes, such as Pd particles supported on different carbons, , Pd/Al 2 O 3 , Pd/In 2 O 3 , Pd/SiO 2 , Pd/DOWEX, and others. , Recently, Ananikov et al reported that Vulcan XC-72 carbon carried 1 wt % Pd particles disclosed with a high turnover number (TON) up to 5000 with a low usage amount of only 0.02–0.3 mol % of Pd for the transfer hydrodebenzylation system with HCO 2 H as the reductant. From the viewpoint of practical applications, development of more cost-effective Pd catalysts is still an attractive topic to debenzylation.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of the physicochemical properties and explosion characteristics of the II-IVgeneration explosives[1,10].…”
mentioning
confidence: 99%